2018
DOI: 10.1039/c7sc04974a
|View full text |Cite
|
Sign up to set email alerts
|

A zeolite-like aluminophosphate membrane with molecular-sieving property for water desalination

Abstract: A fascinating membrane material composed of polycrystalline zeolite-like aluminophosphate with narrow pore and high water uptake is well developed, which exhibits superior desalination performance in terms of excellent ion rejection and record water flux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The nanopores of GO allows water to pass exclusively, while it is impermeable to other chemical species including helium 45 . Other than graphene, composite membranes based on zeolite also have been applied for water desalination [46][47][48][49] . Molecular dynamics simulation study suggested that zeolite with pore size comparable to the first hydrated shell diameter of chloride can be expected to improve salt rejection rate 47 .…”
Section: Nanomaterials As Multifunctional Materials: Research Achievemmentioning
confidence: 99%
“…The nanopores of GO allows water to pass exclusively, while it is impermeable to other chemical species including helium 45 . Other than graphene, composite membranes based on zeolite also have been applied for water desalination [46][47][48][49] . Molecular dynamics simulation study suggested that zeolite with pore size comparable to the first hydrated shell diameter of chloride can be expected to improve salt rejection rate 47 .…”
Section: Nanomaterials As Multifunctional Materials: Research Achievemmentioning
confidence: 99%
“…To understand the mechanism of AlPOs in alkaline media, crystallization of AlPO 4 ‐18 in alkaline media is a typical model that has been carefully investigated . Figure shows the crystallization process of AlPO 4 ‐18 monitored with XRD, SEM, UV‐Raman, and N 2 sorption techniques.…”
Section: Figurementioning
confidence: 99%
“…It can be seen that they have been continuously taken into account; indeed, researchers’ attention to them for such purposes is increasing. To date, zeolites have been considered for different membrane separation applications such as gas separation [ 15 ], pervaporation [ 16 , 17 , 18 ], microfiltration [ 19 ], ultrafiltration [ 20 ], nanofiltration [ 21 ], desalination [ 22 ], water treatment [ 23 , 24 ], and membrane distillation [ 25 ]. Either natural or artificial, zeolites are used for these applications thanks to their unique ion-exchange [ 26 ], adsorption, catalytic, and molecular sieving features.…”
Section: Fundamentals Of Zeolitesmentioning
confidence: 99%